Video analysis of potential head injury situations in FIFA Beach Soccer World Cups - Lima, Y.; Köyagasioglu, O.; Peek, K.; Hovenberg, A.; Karaçoban, L. (Journal of Science and Medicine in Sport, 2026)
Objectives To evaluate potential head injuries across three consecutive FIFA Beach Soccer World Cups held between 2019 and 2024.